Comorbid Conditions in Persons Exposed to Ionizing Radiation and Veterans of the Soviet-Afghan War: A Cohort Study in Kazakhstan - Saule Sarkulova; Roza Tatayeva; Dinara Urazalina; Ekaterina Ossadchaya; Venera Rakhmetova (Korean Society for Preventive Medicine, 2024)
Objectives: This study investigated the prevalence and characteristics of comorbid conditions in patients exposed to ionizing radiation and those who were involved in the Soviet-Afghan war. Methods: This study analyzed the frequency and spectrum of morbidity and comorbidity in patients over a long-term period (30-35 years) following exposure to ionizing radiation at the Semipalatinsk nuclear test site or the Chornobyl nuclear power plant, and among participants of the Soviet-Afghan war. A cohort study, both prospective and retrospective, was conducted on 675 patients who underwent comprehensive examinations. Results: Numerical data were analyzed using the Statistica 6 program. The results are presented as the mean±standard deviation, median, and interquartile range (25-75th percentiles). The statistical significance of between-group differences was assessed using the Student t-test and Pearson chi-square test. A p-value of less than 0.05 was considered statistically significant. We found a high prevalence of cardiovascular diseases, including hypertension (55.0%) and cardiac ischemia (32.9%); these rates exceeded the average for this age group in the general population. Conclusions: The cumulative impact of causal occupational, environmental, and ultra-high stress factors in the combat zone in participants of the Soviet-Afghan war, along with common conventional factors, contributed to the formation of a specific comorbidity structure. This necessitates a rational approach to identifying early predictors of cardiovascular events and central nervous system disorders, as well as pathognomonic clinical symptoms in this patient cohort. It also underscores the importance of selecting suitable methods and strategies for implementing treatment and prevention measures.